Courtyard housing typology in a dense urban area - Moletto Rodríguez, Alberto (el autor, 2009)
In 1992, the suburban population of Santiago became for the first time greater than the population of the city's central area. Since, then the high proportion of citizens in the suburbs has continued to grow: by 2008, the ratio of suburban to urban dwellers had reached 2:1. The fundamental reasons for this migration have been identified as a lack of green areas in the city, and the absence of housing projects with private courtyards. However, even the suburban housing projects that are conceived to cater for the demands of this migration do not demonstrate due consideration of the climatic conditions of the city. The aim of this dissertation project is to create a contemporary re-interpretation of the vernacular three courtyard house typology for the central area of the city, taking into account the thermal performance and formal aspects of this typology.